2022
DOI: 10.3389/fpls.2022.902342
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Potato Tuber Moth-Induced Early-Defense Response by Simulated Herbivory in Potato Plants

Abstract: Plants rely on the perception of a multitude of herbivory-associated cues (HACs) to activate their defense response to insect herbivores. These stimuli are mainly derived from three functional components, namely, mechanical damage, insect-associated microbe, and insect’s chemical cues. While simulated herbivory integrating these stimuli is widely exploited for complementing actual herbivory in clarifying the details of plant–herbivore interaction, breaking down these stimuli and identifying the mechanisms of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…In addition, 24 genes associated with the biosynthetic pathways of volatile terpenoids and HPL-derived green leaf volatiles were upregulated after S. litura infestation, highlighting their potential roles in S. litura-induced pear defenses. Unlike defense-related nonvolatile and volatile secondary metabolites, growth-related photosynthesis was suppressed in S. litura-infested P. betuleafolia (Table S7), which is similar to the findings reported in the defense response of potato (Mao et al, 2022), cotton (Zhang et al, 2022), rice (Wang et al, 2020;Satturu et al, 2021), wheat (Zhang et al, 2020) and tomato (Ke et al, 2021) plants induced by herbivores. In herbivoredamaged plants, suppression of photosynthesis might be a Behavioral preference of Spodoptera litura larvae for (E)-b-ocimene.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, 24 genes associated with the biosynthetic pathways of volatile terpenoids and HPL-derived green leaf volatiles were upregulated after S. litura infestation, highlighting their potential roles in S. litura-induced pear defenses. Unlike defense-related nonvolatile and volatile secondary metabolites, growth-related photosynthesis was suppressed in S. litura-infested P. betuleafolia (Table S7), which is similar to the findings reported in the defense response of potato (Mao et al, 2022), cotton (Zhang et al, 2022), rice (Wang et al, 2020;Satturu et al, 2021), wheat (Zhang et al, 2020) and tomato (Ke et al, 2021) plants induced by herbivores. In herbivoredamaged plants, suppression of photosynthesis might be a Behavioral preference of Spodoptera litura larvae for (E)-b-ocimene.…”
Section: Discussionsupporting
confidence: 87%
“…Plants, especially perennial fruit trees such as pear, are frequently subject to attack by a variety of insect pests. In response to insect herbivore attack, plants have evolved highly sophisticated strategies allowing them to perceive various herbivory-associated molecules from insects’ oral secretions (or regurgitant), oviposition fluids or larval frass and trigger complex defense systems ( Mao et al., 2022 ; Zhang et al., 2022 ). After the recognition of herbivores, plant initiate a series of early signaling events such as V m variation, Ca 2+ elevation, production of reactive oxygen species and activation of MAP kinases, as well as phytohormone-centered regulatory networks to broad transcriptional reprogramming, ultimately leads to the synthesis and accumulation of defensive proteins and defense-associated secondary metabolites ( Erb and Reymond, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Mao et al [20], ROS signaling was activated by PTM-derived herbivoryrelated cues as early as 1 h after treatment. In general, the process of ROS generation occurs within seconds to minutes of stress initiation [58,59], whereas it is possible that the subsequent results might be different in response to the age of PTMs or depending on treatment time.…”
Section: Discussionmentioning
confidence: 98%
“…Numerous studies have shown that JA plays a central role in regulating plant responses to phytophagous insects, while other hormones act in concert or antagonize the JA signaling pathway [1,12]. The selective activation of downstream-related pathways or signals by plants depends on the insect and plant species, and time differences in insect infestation can also lead to dramatic changes in plant defense responses [18][19][20]. Transcription factors play a key regulatory role in the global defense deployment of plants [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation